Collagen scaffolds combined with collagen‐binding ciliary neurotrophic factor facilitate facial nerve repair in mini‐pigs. Issue 5 (18th August 2014) - Lu, Chao; Meng, Danqing; Cao, Jiani; Xiao, Zhifeng; Cui, Yi; Fan, Jingya; Cui, Xiaolong; Chen, Bing; Yao, Yao; Zhang, Zhen; Ma, Jinling; Pan, Juli; et al.
Abstract: The preclinical studies using animal models play a very important role in the evaluation of facial nerve regeneration. Good models need to recapitulate the distance and time for axons to regenerate in humans. Compared with the most used rodent animals, the structure of facial nerve in mini‐pigs shares more similarities with humans in microanatomy. To evaluate the feasibility of repairing facial nerve defects by collagen scaffolds combined with ciliary neurotrophic factor (CNTF), 10‐mm‐long gaps were made in the buccal branch of mini‐pigs' facial nerve. Three months after surgery, electrophysiological assessment and histological examination were performed to evaluate facial nerve regeneration. Immunohistochemistry and transmission electron microscope observation showed that collagen scaffolds with collagen binding (CBD)‐CNTF could promote better axon regeneration, Schwann cell migration, and remyelination at the site of implant device than using scaffolds alone. Electrophysiological assessment also showed higher recovery rate in the CNTF group. In summary, combination of collagen scaffolds and CBD‐CNTF showed promising effects on facial nerve regeneration in mini‐pig models. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 1669–1676, 2015.